2015
DOI: 10.1007/s00259-014-2972-7
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging biomarkers in head and neck cancer

Abstract: In locally advanced head and neck squamous cell carcinoma (HNSCC), the role of imaging becomes more and more critical in the management process. In this framework, molecular imaging techniques such as PET allow noninvasive assessment of a range of tumour biomarkers such as metabolism, hypoxia and proliferation, which can serve different purposes. First, in a pretreatment setting they can influence therapy selection strategies and target delineation for radiation therapy. Second, their predictive and/or prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…A typical tracer for the metabolic uptake of the tumor is FDG for PET imaging [159,160]. The pretreatment maximum standardized uptake value (SUV, which is the normalized FDG uptake for an injected dose according to the patient's body weight) is strongly linked with tumor recurrence as well as overall survival in a number of tumor sites, such as the lung, head and neck, rectum, esophagus and cervix [161][162][163][164][165][166][167]. Additionally, numerous studies have revealed that variations in SUV during and after treatment are initial predictors of tumor recurrence [168][169][170][171].…”
Section: Imaging Features: From Tumor Size To Radiomicsmentioning
confidence: 99%
“…A typical tracer for the metabolic uptake of the tumor is FDG for PET imaging [159,160]. The pretreatment maximum standardized uptake value (SUV, which is the normalized FDG uptake for an injected dose according to the patient's body weight) is strongly linked with tumor recurrence as well as overall survival in a number of tumor sites, such as the lung, head and neck, rectum, esophagus and cervix [161][162][163][164][165][166][167]. Additionally, numerous studies have revealed that variations in SUV during and after treatment are initial predictors of tumor recurrence [168][169][170][171].…”
Section: Imaging Features: From Tumor Size To Radiomicsmentioning
confidence: 99%
“…In addition, for patients who consented to an extra study-specific procedure and when it was logistically feasible, patients underwent an additional mid-therapy pelvic PET/CT (n = 39). This scan was conducted a median (range) of 14 days (7,19) into chemoradiotherapy ( Figure 1). This time point was chosen based on a publication of sequential PET during chemoradiotherapy for locally advanced rectal cancer, 30 showing that assessment at 2 weeks was optimal for discriminating between pathological responders and non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…14 For these cancers, both the FDG-accumulating tumor volume and maximal tumor uptake values have shown associations with treatment outcome and disease-free survival. [15][16][17][18][19][20][21] Previous studies on FDG-PET of anal cancer have addressed the predictive role of PET-derived markers assessed by pre-or posttherapy imaging. [22][23][24][25][26] First, these studies did not evaluate HPV status in the same patient cohort.…”
mentioning
confidence: 99%
“…42 Patients with head-and-neck cancer with high baseline tumour 18 F-fluoromisonidazole uptake are known to have high risk of locoregional failure; 43 however, there is evidence that residual tumour hypoxia, as measured both in pre-clinical models and by 18 F-fluoromisonidazole or 18 F-fluoroazomycinarabinoside PET in several patient cohorts, early in the course of fractionated radiotherapy for head-and-neck cancer both has more potential for therapy adaptation and is a stronger predictor of outcome than baseline hypoxia. [44][45][46][47] Moreover, in this patient group, hypoxia-targeted interventions (e.g. nimorazole or nicotinamide combined with carbogen breathing) have shown promising results, [48][49][50] although the randomized trial of adding tirapazamine to cisplatin-containing CRT in the experimental arm failed to improve overall survival.…”
Section: Molecular Biomarkers Of Tumour Hypoxiamentioning
confidence: 97%